2018
DOI: 10.1016/j.ygyno.2018.04.558
|View full text |Cite
|
Sign up to set email alerts
|

Prospective cohort study comparing quality of life and sexual health outcomes between women undergoing robotic, laparoscopic and open surgery for endometrial cancer

Abstract: Minimally invasive approaches result in improved QOL beyond the short-term postoperative period, with benefits noted up to 12 weeks after surgery. This prolonged QOL advantage provides further evidence that MIS should be the standard surgical approach for women with early stage endometrial cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 29 publications
6
35
0
Order By: Relevance
“…Other trials conducted as single arm studies on HRQoL in robotic surgery for endometrial cancer showed similar outcomes as our trial, with decreased quality of life and negatively affected postoperative symptoms one week after robotic surgery compared to baseline and a return to the preoperative level within five or six weeks after surgery (Arms, et al 2015, Herling, et al 2016a. Ferguson et al investigated prospectively HRQoL between laparoscopic, robotic and open surgery for endometrial cancer and showed similar results as those presented in our study, with improved HRQoL three weeks postoperatively for minimally invasive surgery compared to open surgery (Ferguson, et al 2018). In contrary to our trial, that study was not performed in an ERAS programme and the mean EQ-5D index was not adjusted for postoperative complications, which seem to have a substantial impact on the outcomes.…”
Section: Hrqol and Postoperative Symptomssupporting
confidence: 87%
“…Other trials conducted as single arm studies on HRQoL in robotic surgery for endometrial cancer showed similar outcomes as our trial, with decreased quality of life and negatively affected postoperative symptoms one week after robotic surgery compared to baseline and a return to the preoperative level within five or six weeks after surgery (Arms, et al 2015, Herling, et al 2016a. Ferguson et al investigated prospectively HRQoL between laparoscopic, robotic and open surgery for endometrial cancer and showed similar results as those presented in our study, with improved HRQoL three weeks postoperatively for minimally invasive surgery compared to open surgery (Ferguson, et al 2018). In contrary to our trial, that study was not performed in an ERAS programme and the mean EQ-5D index was not adjusted for postoperative complications, which seem to have a substantial impact on the outcomes.…”
Section: Hrqol and Postoperative Symptomssupporting
confidence: 87%
“…Several studies have shown the adequacy and safety of minimally invasive surgery (MIS) to perform systematic AL, with the advantages of: less postoperative pain; lower incidence of intraoperative and postoperative complications; shorter hospital stay; and improved quality of life …”
Section: Introductionmentioning
confidence: 99%
“…postoperative complications; shorter hospital stay; and improved quality of life. 6,[9][10][11][12] In recent years, robotic technology has further increased the spread of minimally invasive surgery, and many studies have emphasized its safety and further advantages in carrying out some of the most complex surgical procedures. [13][14][15][16][17][18] The main characteristics of robotic technology that facilitate surgical performances also help to shorten the learning curve, including three-dimensional visualization, articulated instrumentation, and stability of the camera.…”
mentioning
confidence: 99%
“…This may indicate the positive effect of using the enhanced recovery after surgery protocol on post-operative recovery 24. Length of stay and time to meet the discharge criteria were equally short in both groups, showing a difference between medical discharge criteria and context-specific social circumstances or demography prolonging hospital stay.…”
Section: Discussionmentioning
confidence: 91%